INNOVATIVE TO THE CORE stories from china and the world. - FERNANDEZ, JUAN ANTONIO (EMERALD GROUP PUBL, 2022)
Based on extensive interviews with industry leaders, Innovative to the Core: Stories from China and the Worlddescribes the components of innovative cultures, including both national culture and organizational culture and how they compare to the China model.